Alkali-Treated, Nanostructured-Micro-Porous Titanium Surfaces Enhance Osteogenic Differentiation of Adipose Derived Stem Cells - Aniruddha Vijay Savargaonkar; Emma Holloway; Ketul C. Popat (Applied Sciences)
Ensuring effective integration between the material of an implant and bone is critical to orthopedic implants’ success in the long term. A major issue with dense materials is the mechanical mismatch between them and the bone, which leads to improper osseointegration. Porous implants have presented a solution to this issue as they are able to retain material properties in addition to decreasing mismatches. In order to make implants more biomimetic and to match the micro-/nano hierarchy of bone, several surface modifications have been explored in the literature. Hydrothermal treatment in an alkali media on dense titanium has demonstrated higher differentiation of adipose-derived stem cells to osteogenic lineages. In this study, we fabricated nanostructures using hydrothermal treatment in an alkali medium on micro-porous titanium surfaces and evaluated the adhesion, proliferation, and differentiation of adipose derived stem cells to osteoblasts. The nanostructured-micro-porous titanium surfaces displayed enhanced osteogenic differentiation of adipose derived stem cells. Therefore, they have the potential to be used as surfaces for the fabrication of orthopedic implants.